2022
DOI: 10.1055/s-0042-1744476
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Simultaneous Bilateral Open Surgery and VATS for Pulmonary Metastasectomy

Abstract: Background Resection is the current treatment of choice for resectable bilateral pulmonary metastases. This study aimed to compare the differences in outcomes between simultaneous bilateral open and video-assisted thoracic surgery (VATS) for pulmonary metastasectomy. Methods Forty-three patients underwent pulmonary metastasectomy through one-stage bilateral open thoracotomy (n = 16) and VATS (n = 27) between 2011 and 2020. Perioperative and oncological data were analyzed. Results The predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In conclusion, one-stage surgery for managing a wide array of thoracic diseases is proven to be safe and efficacious [1][2][3][4][5][6][7][8][9][10]15], and its advantages include circumventing the risk of contralateral tumor progression, comparable wound pain when compared with unilateral-side surgery, decreased medical cost, and decreased psychological burden. In our study, SBTLR allowed clear pathological discrimination in patients with indeterminate lung neoplasms and produced a perioperative course with a comparable safety profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, one-stage surgery for managing a wide array of thoracic diseases is proven to be safe and efficacious [1][2][3][4][5][6][7][8][9][10]15], and its advantages include circumventing the risk of contralateral tumor progression, comparable wound pain when compared with unilateral-side surgery, decreased medical cost, and decreased psychological burden. In our study, SBTLR allowed clear pathological discrimination in patients with indeterminate lung neoplasms and produced a perioperative course with a comparable safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the patient was moved into the contralateral decubitus position for the more complicated operation (i.e., lobectomy or complex segmentectomy). Prioritization of the simpler side allowed for safer resection of the contralateral side, which is an approach based on our experience with simultaneous bilateral surgical treatment of metastases and bronchiectasis [2, 15]. For small neoplasms deemed non‐visible or non‐palpable, we often utilized patent blue dye for preoperative CT‐guided localization of the lesions, before commencing sublobar resections such as wedge resection or simple segmentectomy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the intricacies of thoracic surgery, unilateral procedures have traditionally been favored in clinical practice; however, recent evidence challenges this notion. A study involving 151 patients demonstrated that for individuals without relevant risk factors, bilateral surgeries do not result in increased severity or complications [36], there is a greater body of literature available to substantiate this conclusion [37,38]. However, further controlled trials are still required to substantiate this conclusion.…”
Section: Multiple Ground-glass Nodules Are Observed In the Bilateral ...mentioning
confidence: 99%